(3TaGA GdYdjd aj eSGFd GdbVGA hGdbOQ hGdMceI hGdJYdjd (B/s - (3GHf bje GdLhRjI, eMeO Hf CHj HcQ Hf CjhHs 691-751 (3gLQjs; (3GdLhjOj, OQhjTs ((3HjQhJ (B- (3dHfGf (B:s (3GdecJHI GdYUQjI ,s, 2003)
(3jJfGhd GdcJGH Gddg Ld LdGdg hGdPGJ GdEdgjI hGdbVGA hGdbOQ(B.s
Keywords: (3GdbVGA hGdbOQs; (3GdSeYjGJs -- (3GdbVGA hGdbOQs